Atardecer en el pueblo fantasma - Osborne, Mary Pope.; Murdocca, Sal; Brovelli, Marcela (New York : Lectorum Pub., 2006)
Their magic tree house takes Jack and Annie back to the Wild West, where they experience excitement and danger and try to solve a riddle.
Keywords: Frontier and pioneer life -- West (U.S.) -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Frontier and pioneer life -- West (U.S.) -- Juvenile fiction; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; Spanish language materials; West (U.S.) -- Fiction; West (U.S.) -- Juvenile fiction